2023
DOI: 10.1186/s12889-023-15794-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron-folic acid supplementation and pregnancy-induced hypertension among pregnant women in public hospitals, Wolaita Sodo, Ethiopia 2021: a case- control study

Abstract: Background Pregnancy-induced hypertension is the new onset of high blood pressure after 20 weeks of gestation in women with previously normal blood pressure. To the best of our knowledge, no study has been conducted in our country to investigate the association between this pregnancy problem and iron-folic acid supplementation. The aim of this study was to determine the association between iron-folic acid supplementation and pregnancy-induced hypertension (PIH) in pregnant women at public hospi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Similarly, a curved relationship was observed in the overweight subgroup. Currently, dietary iron intake is mainly focused on pregnancy and anemia among women (25,26). However, it has been shown that dietary iron intake exhibited no relationship with non-pregnancy diseases such as gynecological cancers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a curved relationship was observed in the overweight subgroup. Currently, dietary iron intake is mainly focused on pregnancy and anemia among women (25,26). However, it has been shown that dietary iron intake exhibited no relationship with non-pregnancy diseases such as gynecological cancers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, controversial evidence for nutritional supplementation in reducing PE risk does exist [39,40]. Yet, the overwhelming amount of evidence highlights FA supplementation as a protective factor against PE [12,36,[41][42][43][44].…”
Section: Hypertensive Disordersmentioning
confidence: 99%